A novel method for recovering oil from oily sludge via water-enhanced CO2 extraction. (October 2019) - Wu, Xiao-Fei; Qin, Hui-Bo; Zheng, Yi-Xuan; Zhang, Yu; Chen, Wan; Zuo, Julian Y.; Sun, Chang-Yu; Chen, Guang-Jin
Highlights: CO2 and water composite separation method was proposed for oil separation and recovery from oily sludge. CO2 dissolving and swelling are beneficial to oil separating from mud. The joint effects of CO2 and water under proper stirring promote the oil separation from oily sludge. The suitable operation temperature, pressure, sludge/water ratio and stirring time were 313–323 K, 3–4 MPa, 1:7 and 90 min. Up to 80 wt% of the oil in the oily sludge could be recovered. Abstract: A large amount of oily sludge is being produced in the petroleum industry each year and becoming a serious environment issue. An efficient method for separating oil from oily sludge is of great significance for disposing this hazard. In this study, a novel method—water-enhanced CO2 extraction, was proposed to recover oil from the oily sludge. The oily sludge is mixed with water and CO2 thus allowing the oil to be swollen by CO2 under a certain temperature and pressure, leave the solid particles and float upwards to the top interface of the water phase owing to gravitational forces. A series of experiments were conducted to verify the method, optimize the operation conditions and compare it with the traditional approaches like the ultrasonic treatment, the solvent extraction and the supercritical extraction. The results show that up to 80 wt% of the oil in the oily sludge could be recovered using this new method, which is much higher than that using the traditional methods. The most suitable operation temperature, pressure, sludge/water ratio and stirring time were found to be 313–323 K, 3–4 MPa, 1:7 and 90 min, respectively. The proposed water-enhanced CO2 extraction method is efficient in increasing the oil recovery of oily sludge and decreasing its operation conditions compared with traditional oily sludge treatment methods.